2016
DOI: 10.1016/j.molp.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Metabolic Engineering for Artemisinin Biosynthesis and Effective Malaria Treatment by Oral Delivery of Plant Cells

Abstract: Artemisinin is highly effective against drug-resistant malarial parasites, which affects nearly half of the global population and kills >500 000 people each year. The primary cost of artemisinin is the very expensive process used to extract and purify the drug from Artemisia annua. Elimination of this apparently unnecessary step will make this potent antimalarial drug affordable to the global population living in endemic regions. Here we reported the oral delivery of a non-protein drug artemisinin biosynthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 74 publications
0
64
0
Order By: Relevance
“…In addition, we monitored the formation of the intermediates IP, IPP/DMAPP, GPP, FPP, and GGPP using LC‐MS/MS (Figure S2B). All of the expected products were identified by their electron ionization mass spectra using purchased standards (valencene and limonene), a standard purified in‐house (taxadiene), or from the literature (amorphadiene; Malhotra et al, ) and the MS spectra of the formed products are shown in Figure S2C–F. At the concentrations used, what we suspect was protein precipitation was visible after 24 hr, but was prevented by the addition of 0.025% Tween 20 (w/v; data not shown) in subsequent experiments.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, we monitored the formation of the intermediates IP, IPP/DMAPP, GPP, FPP, and GGPP using LC‐MS/MS (Figure S2B). All of the expected products were identified by their electron ionization mass spectra using purchased standards (valencene and limonene), a standard purified in‐house (taxadiene), or from the literature (amorphadiene; Malhotra et al, ) and the MS spectra of the formed products are shown in Figure S2C–F. At the concentrations used, what we suspect was protein precipitation was visible after 24 hr, but was prevented by the addition of 0.025% Tween 20 (w/v; data not shown) in subsequent experiments.…”
Section: Resultsmentioning
confidence: 96%
“…This may be one of the reasons for the failure to obtain transgenic A. annua lines with high artemisinin content. Recently, a synthetic biology strategy for artemisinin biosynthesis, in which the complete biosynthetic pathway of artemisinic acid, the precursor of artemisinin, is introduced into tobacco plants, has also been reported (Fuentes et al, 2016;Malhotra et al, 2016). However, whether this strategy allows efficient artemisinin production in other plant species needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…The most successful attempt to biosynthetically produce artemisinin took two large sections of the metabolic pathway for artemisinin and genetically engineered them separately into three different cellular compartments (chloroplast, nucleus, and mitochondria). The resulting heterologous expression of artemisinin at ∼0.8 mg/g DW was less than in the native plant, which can reach 31.4 mg/g DW (Zhang et al, 2009;Malhotra et al, 2016). This can in part be explained by the complexity of the gene expression and regulation of the biosynthetic pathway (Ikram and Simonsen, 2017).…”
Section: Molecular Farmingmentioning
confidence: 98%